Antipyretic Activity of Stembark Extract of Mammea africana in Rats - Jude E. Okokon; Chinyelu C. Osigwe; John A Udobang; Uwaeme Ugonma Florence (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Mammea africana Sabine (Guttiferae), is a tree plant whose parts are variously used locally for the treatment of various diseases such as malaria and fever among others. The stembark extract of M. africana (30 -90 mg/kg) was investigated for antipyretic activity in rats using different experimental models; amphetamine, dinitrophenol and yeast-induced pyrexia. The extract exerted prominent inhibition of pyrexia on amphetamine, dinitrophenol and yeast -induced pyrexia. Inhibition was significant (p<0.05–0.001) from 3 to 5 h post- administration of extract and in a dose-dependent fashion. The antipyretic effects of this plant may in part be mediated through the chemical constituents of the plant. The results of this investigation validate the ethnomedical uses of this plant in the treatment of febrile conditions.